2001
DOI: 10.1093/jpepsy/26.5.253
|View full text |Cite
|
Sign up to set email alerts
|

Empirically Supported Treatments in Pediatric Psychology: Regimen Adherence

Abstract: Future studies will need to develop adequate definitions of adherence, accurate methods of assessing adherence, and appropriate designs to evaluate multicomponent treatment programs to advance interventions to the "well-established" category.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
80
0
2

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(85 citation statements)
references
References 42 publications
3
80
0
2
Order By: Relevance
“…75 Among children with asthma, juvenile rheumatoid arthritis, and type 1 diabetes, myriad adherence-intervention strategies have been examined. 76 Educational strategies focus on providing written and verbal information to patients and their families about the illness and the regimen requirements, as well as the importance of adherence and anticipatory coping strategies for potential adverse effects. Organizational strategies emphasize simplifying regimens and changing clinic characteristics such as improving supervision of providers, decreasing waiting times, and boosting accessibility.…”
Section: Recommendations For Improving Adherencementioning
confidence: 99%
See 1 more Smart Citation
“…75 Among children with asthma, juvenile rheumatoid arthritis, and type 1 diabetes, myriad adherence-intervention strategies have been examined. 76 Educational strategies focus on providing written and verbal information to patients and their families about the illness and the regimen requirements, as well as the importance of adherence and anticipatory coping strategies for potential adverse effects. Organizational strategies emphasize simplifying regimens and changing clinic characteristics such as improving supervision of providers, decreasing waiting times, and boosting accessibility.…”
Section: Recommendations For Improving Adherencementioning
confidence: 99%
“…A review of the literature in these diseases revealed that "probably efficacious" strategies include organizational interventions, multicomponent packages, and operant learning and that behavioral, educational, and cognitive-behavioral strategies are "promising." 76 …”
Section: Recommendations For Improving Adherencementioning
confidence: 99%
“…An evidence review by Lemanek et al 47 on asthma adherence suggested that some educational and behavioral strategies are "probably efficacious" in creating change. In addition, a study that used cognitive behavioral strategies suggested that diabetic adherence can also be improved.…”
Section: Initial Management Of Adolescent Depressionmentioning
confidence: 99%
“…Further, poor adherence results in increased morbidity and mortality, as well as problematic medication use and excessive use of health care services. [4,5] Numerous factors have a significant impact on adherence and glycemic control.…”
Section: The Challenges Of Type 1 Diabetesmentioning
confidence: 99%